Knowledge and attitude towards long acting- reversible contraceptive (LARC) among married women who attended the outpatient clinic at Hospital Pakar Universiti Sains Malaysia (HPUSM) - Ismail, Nur Atiqah (Universiti Sains Malaysia, 2025)
Long-acting reversible contraceptives (LARC) are modern contraceptive methods known for their high effectiveness and long-term protection with minimal user intervention. This study aimed to assess the level of knowledge and attitude towards LARC among married women who attended the outpatient clinic at Hospital Pakar Universiti Sains Malaysia (HPUSM). A cross-sectional study was conducted at HPUSM from January to March 2025 involving 136 conveniently selected married women, using a self-administered questionnaire to assess their knowledge and attitude. The questionnaire included items on socio-demographic data, knowledge of LARC methods (such as IUCD and Implanon), and attitudes regarding their use. The findings showed that 32.4% of respondents had high knowledge, 39.7% moderate, and 27.9% low knowledge; while 30.1% had a positive attitude, 24.3% moderate, and 45.6% negative attitude toward LARC. The mean age of respondents was 35 years (SD = 7.89), ranging from 19 to 49 years. A significant association was found between knowledge and attitude levels (p < 0.001), and socio-demographic factors such as age, occupation, education, and parity were also significantly associated with knowledge and attitude (p < 0.05). In conclusion, although general awareness of LARC exists among married women at HPUSM, detailed knowledge and positive attitudes remain limited, highlighting the need for targeted educational interventions to improve informed contraceptive choices